Fee-Free Education Policy and Students Performance in Public Secondary Schools in Tanzania: The Role of Parental Involvement - Minja, Liberia Josephat; Mkulu, Demetria; Chuwa, Agapiti H.; Mhemera, Passian; Osaki, Kalafunja (International Journal For Research In Educational Studies, 2020)
In 2014, the government of the United Republic of Tanzania issued ‘Education and Training Policy’ directing authorities to ensure education provided in public secondary schools is free of charge in a move to lessen burden shouldered by parents. Nevertheless, the ‘fee-free education policy’ is possibly misunderstood by parents as they no longer show interest in participating in school matters. How this affects students’ academic performance has remained unknown. This study investigated students’ academic performance and role of parents in building effective school climate in public secondary schools after implementation of the fee-free education policy. A sample of 83 participants including 40 students, 29 teachers, 10 parents and four heads of schools were involved. Data were collected using structured questionnaires and interview guides. Archived data were extracted from Ilala Municipality’s database in the city of Dar es Salaam. We used SPSS version 20.0 to code and analyze quantitative data using descriptive statistics and reported the results in frequencies, tables, pie charts, bar graphs and histograms. Content analysis was employed to analyze qualitative data. The results showed a slight increase in students’ enrolment in Form I. Notwithstanding, no significant change observed in students’ academic performance during the four years, 2014-2018 and, the number of students who complete Form IV secondary education is declining. Moreover, among the respondents, 82% agreed that, interpersonal relationship among teachers, parents and students is necessary to promote students’ academic performance and 66% indicated that parental involvement is imperative to foster students’ learning. Lack of dormitories/ hostels for students and inadequate libraries were noted as main factors affecting students’ performance. Taken together, the findings of the current study suggest that providing free education alone does not improve students’ academic performance in public secondary schools in Tanzania, therefore, government and educational stakeholders, including parents should take immediate action to ensure conducive learning environment and availability of resource centers in public secondary schools.